Pedagogical reflections on learning languages in instructed settings - Usó Juan, Esther; Ruiz-Madrid, Ma Noelia (Cambridge Scholars Pub., 2007)
Pedagogical Reflections on Learning Languages in Instructed Settings is intended to provide the latest pedagogical reflections that derive from research in a variety of key areas within the discipline of language learning. Thus, this volume aims at helping practising language teachers to update their teaching methodology. The book has fifteen chapters that are grouped around five sections. The first section of the book includes three chapters, which outline past approaches to language learnin ...